The ripple effect of flooding near one of the more prominent urban rivers in the Gauteng Province, South Africa - Raphela, Tlou D. (Frontiers in Sustainable Cities, 2025)
The Jukskei River in Gauteng Province, South Africa, has experienced recurrent flooding over the past decade, severely impacting nearby communities. While environmental and socio-economic effects are well documented, the psychological impacts in the Global South remain underexplored. Using a positivist paradigm, this quantitative study employed a structured questionnaire administered to 100 purposively selected residents of the Setswetla informal settlement. The sample was drawn from a list of flood-affected households provided by the City of Johannesburg disaster management officials. Data were analysed in R using Chi-Square Tests of Independence and Binary Logistic Regression to examine links between demographics, environmental perceptions, economic losses, and mental health outcomes, including PTSD, vicarious trauma, and compassion fatigue. Employment status was significantly associated with perceptions of environmental damage (p = 0.028). Displacement (p = 0.024) and job loss (p = 0.001) were strong predictors of reported economic loss. PTSD prevalence was linked to disturbing dreams, emotional numbness, and memory disruption. Vicarious trauma (χ2 = 78.18; df = 13; p < 0.000) and compassion fatigue (χ2 = 94.53; df = 20; p < 0.001) were significantly related to PTSD status, indicating a cumulative mental health burden from recurrent flooding. Recurrent flooding in Setswetla generates interconnected environmental, economic, and mental health impacts. Integrated disaster risk reduction should address infrastructure, livelihoods, and community-based mental health support. Early identification and treatment of PTSD and related conditions should be embedded in post-flood recovery programs for flood-prone informal settlements.